2018
DOI: 10.3390/met8070524
|View full text |Cite
|
Sign up to set email alerts
|

Research on Surface Roughness of AlSi10Mg Parts Fabricated by Laser Powder Bed Fusion

Abstract: AlSi10Mg cubes were fabricated with the laser powder bed fusion (LPBF) process, using different exposure times and scan strategies to gain insight into the effect of energy density and part orientation on surface roughness. The results showed that, with increasing energy density, the five-face roughness first decreased and then increased, whereas the top roughness increased slightly. Moreover, considerable differences in roughness appeared for the different faces. A good surface quality was obtained at 175 J/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…It was found that the surface roughness on the gas-averted surfaces (Sa = 17.1 ± 1.7 µm) is higher than on the gas-facing surfaces (Sa = 14.8 ± 1.8 µm). This result agrees with findings from similar investigations (Li et al, 2018).…”
Section: Correlation Between Defects and Propertiessupporting
confidence: 94%
“…It was found that the surface roughness on the gas-averted surfaces (Sa = 17.1 ± 1.7 µm) is higher than on the gas-facing surfaces (Sa = 14.8 ± 1.8 µm). This result agrees with findings from similar investigations (Li et al, 2018).…”
Section: Correlation Between Defects and Propertiessupporting
confidence: 94%
“…Additionally, as observed by X-ray computed tomography, porosity distribution has not shown any pattern that can be related to stress relaxation (see Figure 5c in [13]). As shown in [35] for LPBF AlSi10Mg, the two surfaces facing Ar flow output (surface 2) and opposite to it (surface 4) have the highest difference in the roughness. In our case, roughness measurements were performed at each lateral surface and summarized in Table 2.…”
Section: Effect Of Sample Orientation With Respect To Ar Flowmentioning
confidence: 83%
“…However, L-PBF technology has several limitations, particularly related to the poor surface finish and the need for final post-processing of the manufactured parts [10]. The parts manufactured using L-PBF show roughness values Ra between 3.2 and 12.5 µm [13], whereas conventional technologies obtain roughness values between 1-2 µm [11].…”
Section: Of 12mentioning
confidence: 99%
“…In addition, excessive laser power will lead to higher porosity. Thus, it is necessary to find a balance between the laser power and scan speed to ensure acceptable roughness and other properties such as porosity [11,12,23]. In addition, another process parameter that influences the roughness is the thickness of the layer used [27].…”
Section: Of 12mentioning
confidence: 99%
See 1 more Smart Citation